Outcomes and Risk Factors Associated with Burn Injuries in Children - Ebrahimi 1, Mehdi; Sohrabi 2*, Mohammad Bagher; Zolfaghari 2, pouneh; Yahyaei 2, Elahe; Nick kheslat 2, Nasim; Shariati 2, Zahra; Sohrabi 3, Sina (Shahroud Journal of Medical Sciences, 2016)
Background: Burn injuries and their complications are still considered major threats to society’s health standards. The aim of this study was to describe the epidemiological profile, outcome, and factors associated with children’s burn injuries in Shahroud (northeastern Iran). Methods: This cross-sectional study was performed over a three-year period (2013–2015) on children 12 years and under who were admitted to Imam Hossein Hospital in Shahroud with burn injuries. In this study, we reviewed medical records of hospitalized burn patients, and an analysis was performed using SPSS software. Results: Of the 195 patients, 111 cases (56.9%) were male and the rest were female. The mean age was 6.34 ± 5.32 years (0–12 years). The highest proportion of burn injuries were in the 5- to 8-year-old group (47.2%), and the most common environment in which burn injuries occurred was the home (72.3%). The most common cause of burns was a hot liquid (56.9%). The mean TBSA was 20.11 ± 10.5% and the mean LHS was 9.81 ± 3.85 days. The most frequent burn areas were the upper limbs (46.6%), and second-degree burns were the most common type (48.2%). The mortality rate was 10.8%.Conclusions: The results of this study show that burn injuries in the pediatric population most commonly occur at home from a hot liquid, resulting in second-degree burns on upper-limb areas. So a large percentage of them are preventable with a little attention.